Promising role for mesenchymal stromal cells in coronavirus infectious disease-19 (COVID-19)-related severe acute respiratory syndrome?. (March 2021) - Hamdan, Hamdan; Hashmi, Shahrukh K.; Lazarus, Hillard; Gale, Robert Peter; Qu, Wenchun; El Fakih, Riad
Abstract: Mesenchymal stromal cells (MSC) have immune regulatory and tissue regenerative properties. MSCs are being studied as a therapy option for many inflammatory and immune disorders and are approved to treat acute graft-versus-host disease (G v HD). The severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) pandemic and associated coronavirus infectious disease-19 (COVID-19) has claimed many lives. Innovative therapies are needed. Preliminary data using MSCs in the setting of acute respiratory distress syndrome (ARDS) in COVID-19 are emerging. We review mechanisms of action of MSCs in inflammatory and immune conditions and discuss a potential role in persons with COVID-19. Highlights: The severe acute respiratory syndrome coronavirus 2 may cause fatal complications These inflammatory complications can affect any organ, particularly the lungs The disease caused by SARS-CoV-2 is called Coronavirus Infectious disease 2019 (COVID-19) This disease has no approved therapies in any country Mesenchymal stromal cells are being evaluated in clinical trials for COVID-19